2020
DOI: 10.1371/journal.pntd.0008381
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Study of Sepsis in Takeo Province Cambodia: An in-depth examination of pathogens causing severe infections

Abstract: The world’s most consequential pathogens occur in regions with the fewest diagnostic resources, leaving the true burden of these diseases largely under-represented. During a prospective observational study of sepsis in Takeo Province Cambodia, we enrolled 200 patients over an 18-month period. By coupling traditional diagnostic methods such as culture, serology, and PCR to Next Generation Sequencing (NGS) and advanced statistical analyses, we successfully identified a pathogenic cause in 46.5% of our cohort. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…The most common positive microbiologic results overall included bacteraemia (N=83), respiratory culture growth (N=19), serum hepatitis B surface antigen (N=15), and malaria rapid diagnostic tests (N=11). A minority (121 of 567, 21.3%) of subjects had confirmed infections with complete adjudicator agreement using all available sources of clinical microbiologic results (with the notable addition of RNA sequencing of samples from Cambodia 14 ) including 90 (15.9%) bacterial, 17 viral (3.0%), 20 malarial (3.5%), and 2 (0.3%) fungal infections identified across all cohorts ( Supplementary Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common positive microbiologic results overall included bacteraemia (N=83), respiratory culture growth (N=19), serum hepatitis B surface antigen (N=15), and malaria rapid diagnostic tests (N=11). A minority (121 of 567, 21.3%) of subjects had confirmed infections with complete adjudicator agreement using all available sources of clinical microbiologic results (with the notable addition of RNA sequencing of samples from Cambodia 14 ) including 90 (15.9%) bacterial, 17 viral (3.0%), 20 malarial (3.5%), and 2 (0.3%) fungal infections identified across all cohorts ( Supplementary Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Microbiologic results were available if collected through routine clinical care across cohorts. Additional molecular testing and next generation sequencing for pathogens were also performed on blood samples in the Cambodia cohort as previously described 14 . Participants were followed throughout their hospitalization and a record review performed at discharge.…”
Section: Frommentioning
confidence: 99%
See 1 more Smart Citation
“…are important zoonotic pathogens with approximately 500,000 globally reported cases annually, with high lethality depending on species, strain, and case severity (Esson et al., 2019; Song et al., 2021). Exposure to Leptospira has been demonstrated in humans with unexplained sepsis in Cambodia and in people with undifferentiated febrile illness in Northern Thailand (Rozo et al., 2020; Takhampunya et al., 2019). Moreover, the latter study demonstrated the presence of Leptospira DNA in small mammal, vector, and human populations, highlighting the significance of vector species to provide a conduit for animal‐to‐human transmission in Southeast Asia (Takhampunya et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The panel included: IL-6, CXCL10, IL-1RA, D-dimer, procalcitonin, ferritin, VEGF-A, IL-5, soluble receptor for advanced glycation end-product (RAGE), TNFR1, IFN-γ, and C-reactive protein (CRP). This panel was selected to include analytes in clinical use for prognostication (i.e., CRP, procalcitonin, ferritin, and D-dimer)(11), based on prior COVID-19 literature (i.e., IL-6, IFN-γ and CXCL10) (15), and identified to be representative of prior TDA-based non-COVID-19 sepsis clusters (i.e., IL-1RA, VEGF-A, IL-5, RAGE, and TNFR1) (10, 16). All protein concentrations were log 10 -transformed and normalized for site-to-site variation using the R package SVA ComBat (17).…”
Section: Methodsmentioning
confidence: 99%